2016
DOI: 10.1248/cpb.c15-00706
|View full text |Cite
|
Sign up to set email alerts
|

Stability of β-Lapachone upon Exposure to Various Stress Conditions: Resultant Efficacy and Cytotoxicity

Abstract: Even though β-lapachone is a promising compound with antitumor, antiinflammatory, antineoplastic, and wound-healing effects, there are still issues concerning its chemical stability and degradation mechanisms. The objective of this study was to obtain degradation profiles of β-lapachone and evaluate its chemical stability under various stress conditions. Moreover, the correlation between stability and efficacy was evaluated. The degradation study of β-lapachone was performed using heat, acid, base, oxidation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…β-Lapachone (β-Lap) is a natural compound extracted from the lapacho tree abundantly found in Brazil. It exhibits a large variety of promising pharmacological effects including antiparasitic, anti-inflammatory, antibacterial, , and antitumor. , β-Lapachone has been shown to induce apoptosis in prostate, lung, pancreatic, and breast cancer cells. Despite its acknowledged therapeutic potential, its poor stability and low water solubility (160 μM) on the one hand and its toxicity at high doses on the other hand have limited its clinical use so far . A clear need has emerged that, as a drug, β-Lap should be properly formulated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-Lapachone (β-Lap) is a natural compound extracted from the lapacho tree abundantly found in Brazil. It exhibits a large variety of promising pharmacological effects including antiparasitic, anti-inflammatory, antibacterial, , and antitumor. , β-Lapachone has been shown to induce apoptosis in prostate, lung, pancreatic, and breast cancer cells. Despite its acknowledged therapeutic potential, its poor stability and low water solubility (160 μM) on the one hand and its toxicity at high doses on the other hand have limited its clinical use so far . A clear need has emerged that, as a drug, β-Lap should be properly formulated.…”
Section: Introductionmentioning
confidence: 99%
“…7−11 Despite its acknowledged therapeutic potential, its poor stability and low water solubility (160 μM) on the one hand and its toxicity at high doses 12 on the other hand have limited its clinical use so far. 13 A clear need has emerged that, as a drug, β-Lap should be properly formulated. Cavalcanti et al 14 reported its encapsulation into unilamellar vesicles consisting of soybean lecithin (containing about 92% PC(18:2/18:2)), cholesterol (CHOL), and stearylamine (SA) in a 7:2:1 molar ratio at pH 7.4.…”
Section: ■ Introductionmentioning
confidence: 99%